The Praxis of Grammatical Approach in EFL class, from Theory to Pedagogic - Nurul Azizah Ria Kusrini; Nahdiyatul Ummah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Definitions of grammar often refer to the study of language as a system of words that demonstrate some apparent rule of structure and arrangement into sentences. Sometimes the definition includes pronunciation, meaning of words, and history of words (etymology). Some definitions emphasize grammar as a system of rules in a language. In simplest term, grammar covers the rules that govern the way our communication system works. In order to meet the need of grammar teaching, in pedagogical field, there have been some methods and approach which are applied. However, critics pertaining to the weaknesses of such methodology have been aroused. The main question as the result of the quest for better methodology for grammar teaching is what appropriate method or approach as an alternative way of grammar teaching is. This theoretical research is aimed to propose the influential alternative approach for grammar teaching. This study will start by describing the historical view of grammar teaching and pointing out the link between language input and pedagogical mediation, in plain language between grammars and teaching, by introducing and redefining the concept of pedagogical grammar. Eventually, as the ultimate aim of this research this study is going to explain the current development of grammar teaching, lexical approach, as the problem solver concerning with grammar teaching.